Epidemiology of first and recurrent venous thromboembolism in patients with active cancer - Cohen, Alexander T.; Katholing, Anja; Rietbrock, Stephan; Bamber, Luke; Martinez, Carlos (Thrombosis and Haemostasis, 2017)
Population studies on the incidence of venous thromboembolism (VTE) in patients with active cancer are limited. An observational cohort study was undertaken to estimate the incidence of first and recurrent VTE. The source population consisted of all patients in the UK Clinical Practice Research Datalink, with additional information on hospitalisation and cause of death, between 2001 and 2011. A cancer-related clinical diagnosis or therapy within the 90 days before or after a VTE constituted an active-cancer-associated VTE. Incidence rates of first VTE among patients with active cancer and incidence rates of recurrent VTE during the 10-year observational period after a first VTE event were estimated. Incidence rates of all-cause mortality and age- and gender-specific mortality were also calculated. There were 6,592 active-cancer-associated VTEs with a total of 112,738 cancer-associated person-years of observation. The incidence rate of first VTE in patients with active cancer was 5.8 (95 % confidence interval 5.7–6.0) per 100 person-years. A first VTE recurrence was observed in 591 patients. The overall incidence rate for recurrence was 9.6 (95 % confidence interval 8.8–10.4) per 100 person-years, with a peak at 22.1 in the first six months. Recurrence rates were similar after initial pulmonary embolism and after initial deep-vein thrombosis. The mortality risk after VTE was considerable, with 64.5 % mortality after one year and 88.1 % after 10 years. VTE in patients with active cancer is common and associated with high recurrence and mortality rates. Efforts are needed to prevent VTE and reduce recurrence, especially in the first year after VTE diagnosis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Active cancer; venous thromboembolism incidence; recurrence; mortality